2022
DOI: 10.3389/fmed.2022.907334
|View full text |Cite
|
Sign up to set email alerts
|

Agreement Between Predicted and Actual Measured Ablation Depth After FS-LASIK Using Different Rotating Scheimpflug Cameras and OCT

Abstract: PurposeTo compare the predicted ablation depth (AD) with the postoperatively measured corneal ablation depth (postop-AD) at central, paracentral, and midperipheral locations using two rotating Scheimpflug analyzers and a Fourier-domain optical coherence tomographer in eyes that underwent femtosecond laser-assisted LASIK (FS-LASIK).MethodsThe values of corneal thickness were measured preoperatively and postoperatively at one and three months. The difference between preoperative and postoperative was defined as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
1
0
0
Order By: Relevance
“…Many studies have found differences between the measured ablation depth 1 month post FS-LASIK and the preoperative predicted corneal ablation depth [ 8 19 ], and our study confirmed this 1 day postoperatively. The measured ablation depth of the laser platform ablation 1 day after FS-LASIK in the 109 eyes included in this study was 2.49 ± 9.54 μm higher than the predicted value ( p = 0.008).…”
Section: Discussionsupporting
confidence: 87%
“…Many studies have found differences between the measured ablation depth 1 month post FS-LASIK and the preoperative predicted corneal ablation depth [ 8 19 ], and our study confirmed this 1 day postoperatively. The measured ablation depth of the laser platform ablation 1 day after FS-LASIK in the 109 eyes included in this study was 2.49 ± 9.54 μm higher than the predicted value ( p = 0.008).…”
Section: Discussionsupporting
confidence: 87%
“…У попередніх опублікованих дослідженнях було відмічено, що зміни товщини епітелію корелюють зі ступенем гіперметропічної корекції; товщина центрального епітелію тонша, а товщина парацентрального епітелію товстіша для вищих ступенів гіперметропії [27][28][29][30][31][32]. Це подібно до епітеліальних змін, які спостерігаються після міопічних абляцій, коли спостерігалося більше центрального потовщення епітелію для вищих міопічних корекцій, що може частково пояснити, чому спостерігається більший регрес при вищих вихідних показниках аметропії [10][11][12][13][14][15][16][17]. У поточне дослідження не було включено пацієнтів з гіперметропією високого ступеня, але незначний гіперметропічний зсув був зафіксований в обох групах спостереження, при цьому не було відмічено статистично значимої різниці між двома дослідними групами.…”
Section: обговоренняunclassified
“…Будь-яка зміна форми стромальної поверхні рогівки призводить до зміни профілю товщини епітелію, і градієнт кривизни та величина зміни кривизни впливають на ремоделювання епітелію. Була опублікована велика кількість робіт про потовщення центрального епітелію після міопічної ексимерної лазерної абляції, що було пов'язано з міопічним регресом [10][11][12][13][14][15][16][17][18][19]. З огляду на численні дослідження щодо змін товщини епітелію після міопічної ексимерлазерної абляції цілком ймовірно, що епітеліальні зміни також спостерігатимуться після гіперметропічної абляції і також можуть бути пов'язані з регресом рефракційного результату.…”
unclassified